Novel application of nanozeolite for radioactive cesium removal from high-salt wastewater. (15th May 2016) - Lee, Keun-Young; Kim, Kwang-Wook; Park, Minsung; Kim, Jimin; Oh, Maengkyo; Lee, Eil-Hee; Chung, Dong-Yong; Moon, Jei-Kwon
Abstract: Finding a striking peculiarity of nanomaterials and evaluating its feasibility for practical use are interesting topics of research. We investigated the application of nanozeolite's outstanding reactivity for a rapid and effective method for radioactive cesium removal in the wastewater generated from nuclear power plant accident, as a new concept. Extremely fast removal of cesium, even without stirring, was achieved by the nanozeolite at efficiencies never observed with bulk materials. The nanozeolite reached an adsorption equilibrium state within 1 min. Cesium adsorption by nanozeolite was demonstrated at reaction rates of orders of magnitude higher than that of larger zeolite phases. This observation was strongly supported by the positive correlation between the rate constant ratio (k2, bulk /k2, nano ) and the initial Cs concentrations with a correlation coefficient (R 2 ) of 0.99. A potential drawback of a nanoadsorbent is the difficulty of particle settling and separation because of its high dispersivity in solution. However, our results also demonstrated that the nanozeolite could be easily precipitated from the high-salt solution with ferric flocculant. The flocculation index reached a steady state within 10 min. A series of our experimental results met the goal of rapid processing in the case of emergency by applying the well-suited nanozeolite adsorption and flocculation. Graphical abstract: Highlights: We investigated nanozeolite's outstanding reactivity for removal of radiocesium. Extremely fast kinetics of radiocesium removal was achieved by the nanozeolite. Nanozeolite clearly outperformed the bulk zeolite at the actual level of radiocesium. Well-suited nanozeolite adsorption and flocculation were demonstrated.